Polymorphs and cocrystals of cardiac troponin activators
The problems of stability and application are solved by preparing and characterizing various crystalline forms of Compound A, providing effective pharmaceutical compositions for the treatment of heart failure, improving the therapeutic effect.
Patent Information
- Application Number
- CN202080034322.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-12
- Filing Date
- 2020-03-12
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2040-03-12
AI Technical Summary
The lack of different chemical and physical forms of the stable compound A, especially the preparation and application of its salt and crystalline forms, is difficult to effectively be used in the treatment of cardiac troponin activators.
Provides a variety of crystalline forms of Compound A, including free bases, salts, solvates and co-crystals, and their structure and stability are characterized by technical means such as X-ray powder diffraction, differential scanning calorimetry, thermogravimetric analysis and dynamic vapor adsorption. , various physical and chemically stable forms were prepared.
The preparation and characterization of various crystalline forms of Compound A is achieved, and a pharmaceutical composition for the treatment of heart failure is provided, which improves the stability and therapeutic effect of the drug.
Smart Images

Figure BDA0003342380890000011 
Figure BDA0003342380890000051 
Figure BDA0003342380890000261
Abstract
Description
Background Art
[0001] The compound (1R,3R,5R)-N-((R)-cyclopropyl(2,5-difluoro-4-(trifluoromethyl)phenyl)methyl)-2-(5-(methylsulfonyl)nicotinoyl)-2-azabicyclo[3.1.0]hexane-3-carboxamide can be used as a cardiac troponin activator:
[0002]
[0003] There is a need for various novel salts and crystalline forms of Compound A having different chemical and physical stabilities, and the formulations and uses of the various novel salts and crystalline forms. Summary of the invention
[0004] Provided herein are crystalline forms of compound A or its salts, including free alkali crystalline forms, crystalline salts, and crystalline solvates. In some embodiments, provided herein are free alkali anhydrous crystalline forms I of compound A. In some embodiments, provided herein are free alkali anhydrous crystalline forms II of compound A. In some embodiments, provided herein are free alkali monohydrate crystalline forms III of compound A. In some embodiments, provided herein are free alkali anhydrous crystalline forms IV of compound A. In some embodiments, provided herein are crystalline forms of compound A hydrochloride. In some embodiments, provided herein are crystalline forms of compound A and dichloromethane. In some embodiments, provided herein are crystalline forms of compound A and nitromethane. In some embodiments, provided herein are crystalline forms of compound A and hexafluoro-2-propanol.
[0005] Also provided herein are co-crystals comprising Compound A and a coformer. In some embodiments, the coformer comprises propyl gallate. In some embodiments, the coformer comprises glycerol. In some embodiments, the coformer comprises propylene glycol. In some embodiments, the coformer comprises maltol. In some embodiments, the coformer comprises urea.
[0006] Also provided is a pharmaceutical composition comprising a crystalline form or co-crystal of Compound A or a salt thereof as disclosed herein and a pharmaceutically acceptable carrier.
[0007] Also provided is a method of treating heart failure in a subject in need thereof, the method comprising administering to the subject a crystalline form or co-crystal of Compound A or a salt thereof disclosed herein in an amount effective to treat heart failure. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 The X-ray powder diffraction ("XRPD") pattern of the free base anhydrous crystalline Form I is depicted.
[0009] Figure 2 Depicted are Differential Scanning Calorimetry ("DSC") thermograms of the free base anhydrous crystalline Form I and Form II.
[0010] Figure 3 A thermogravimetric analysis ("TGA") trace of the free base anhydrous crystalline Form I is depicted.
[0011] Figure 4 Depicted is a Dynamic Vapor Sorption ("DVS") graph of the free base anhydrous crystalline Form I.
[0012] Figure 5 Depicted is the XRPD pattern of the free base anhydrous crystalline Form II.
[0013] Figure 6 Depicted is the XRPD pattern of the free base monohydrate crystalline Form III.
[0014] Figure 7 Depicted is the DSC thermogram of the free base monohydrate crystalline Form III.
[0015] Figure 8 The TGA trace of the free base monohydrate crystalline Form III is depicted.
[0016] Fig. 9 Depicted is a DVS pattern of the free base monohydrate crystalline Form III.
[0017] Fig.10 Depicted is the XRPD pattern of the free base anhydrous crystalline Form IV.
[0018] Fig.11 Depicted is the DSC thermogram of the free base anhydrous crystalline Form IV.
[0019] Fig.12 The TGA trace of the free base anhydrous crystalline Form IV is depicted.
[0020] Fig.13 Depicted is a DVS diagram of the free base anhydrous crystalline Form IV.
[0021] Fig.14 Depicted are overlays of the XRPD patterns of free base Forms I (upper), II (upper middle), III (lower middle), and IV (lower).
[0022] Fig.15 Depicted is an overview of the thermodynamic relationships between the free base forms I, II, III and IV.
[0023] Fig.16 Depicted is the XRPD pattern of the crystalline form of the hydrochloride salt.
[0024] Fig.17 Depicted is the DSC thermogram of the crystalline form of the hydrochloride salt.
[0025] Fig.18 The TGA trace of the crystalline form of the hydrochloride salt is depicted.
[0026] Fig.19 Depicted is a DVS diagram of the crystalline form of the hydrochloride salt.
[0027] Fig. 20 Depicted are the XRPD patterns of a crystalline form of Compound A and dichloromethane.
[0028] Fig.21 Depicted is the DSC thermogram of a crystalline form of Compound A and dichloromethane.
[0029] Fig. 22 Depicted are the TGA traces of the crystalline form of Compound A and dichloromethane.
[0030] Fig.23 Depicted are the XRPD patterns of a crystalline form of Compound A and nitromethane.
[0031] Fig.24 Depicting the DSC thermogram of a crystalline form of Compound A and nitromethane.
[0032] Fig.25 Depicted is the TGA trace of a crystalline form of Compound A and nitromethane.
[0033] Fig.26 Depicted are XRPD patterns of Compound A and a crystalline form of hexafluoro-2-propanol.
[0034] Fig. 27 Depicting DSC thermograms of crystalline forms of Compound A and hexafluoro-2-propanol.
[0035] Fig.28 Depicted are TGA traces of Compound A and a crystalline form of hexafluoro-2-propanol.
[0036] Fig.29 Depicted is the XRPD pattern of a co-crystal of Compound A and propyl gallate.
[0037] Fig.30 Depicting the DSC thermogram of the co-crystal of Compound A and propyl gallate.
[0038] Fig.31 Depicted is the TGA trace of the co-crystal of Compound A and propyl gallate.
[0039] Fig.32 Depicted is the XRPD pattern of co-crystals of Compound A and glycerol.
[0040] Fig.33 Depicting the DSC thermogram of the co-crystal of Compound A and glycerol.
[0041] Fig.34 Depicted is the TGA trace of the co-crystal of Compound A and glycerol.
[0042] Fig.35 Depicted is the XRPD pattern of the co-crystal of Compound A and propylene glycol.
[0043] Fig.36 Depicting the DSC thermogram of the co-crystal of Compound A and propylene glycol.
[0044] Fig.37 Depicted is the TGA trace of the co-crystal of Compound A and propylene glycol.
[0045] Fig.38 Depicting the XRPD pattern of co-crystals of Compound A and maltol.
[0046] Fig.39 DSC thermogram depicting the co-crystal of Compound A and maltol.
[0047] Fig.40 Depicted is the TGA trace of the co-crystal of Compound A and maltol.
[0048] Fig.41 Depicted is the XRPD pattern of co-crystals of Compound A and urea.
[0049] Fig.42 Depicting the DSC thermogram of co-crystals of Compound A and urea.
[0050] Fig.43 Depicted is the TGA trace of the co-crystal of Compound A and urea.
[0051] Fig.44 The XRPD pattern of the amorphous form of Compound A is depicted.
[0052] Fig.45 The TGA trace of the amorphous form of Compound A is depicted. DETAILED DESCRIPTION
[0053] The present disclosure provides polymorphs and co-crystals of (1R,3R,5R)-N-((R)-cyclopropyl(2,5-difluoro-4-(trifluoromethyl)phenyl)methyl)-2-(5-(methylsulfonyl)nicotinoyl)-2-azabicyclo[3.1.0]hexane-3-carboxamide, referred to herein as “Compound A”, and having the following structure:
[0054]
[0055] Embodiments of the free base form, salt form, solvate, co-crystal, and amorphous form of Compound A may be characterized by one or more of the parameters described in more detail below.
[0056] Free base crystalline form of compound A
[0057] Provided herein are free base crystalline forms of Compound A. In embodiments, the free base crystalline form of Compound A may be a non-ionic form of Compound A. In embodiments, the free base crystalline form of Compound A may be anhydrous. In embodiments, the free base crystalline form of Compound A may be a monohydrate.
[0058] Free base anhydrous crystalline form I
[0059] The free base anhydrous crystalline Form I of Compound A ("Form I") can be characterized by an X-ray powder diffraction pattern obtained as described in the Examples using Cu Ka radiation with peaks at about 9.78, 12.45, 15.70, 16.46, and 16.94 ± 0.2 ° 2θ. Optionally, Form I can also be characterized by an X-ray powder diffraction pattern using Cu Ka radiation with additional peaks at about 8.23, 24.40, 25.03, 25.49, and 32.03 ± 0.2 ° 2θ. Optionally, Form I can also be characterized by an X-ray powder diffraction pattern using Cu Ka radiation with additional peaks at about 19.56, 20.11, 22.99, 23.97, 29.53, 41.91, and 42.83 ± 0.2 ° 2θ. Optionally, Form I can be characterized by an X-ray powder diffraction pattern having the peaks shown in Table 1 set forth in the Examples. In some embodiments, Form I has substantially Figure 1 The X-ray powder diffraction pattern shown in , where by "substantially" it is meant that the reported peaks may vary by about ±0.2°. It is well known in the XRPD art that while the relative peak heights in a spectrum depend on many factors, such as sample preparation and instrument geometry, the peak positions are relatively insensitive to experimental details.
[0060] A differential scanning calorimetry (DSC) thermogram of Form I was obtained as described in the Examples. The DSC curve indicates an endothermic transition at about 152°C ± 3°C. Thus, in some embodiments, Form I may be characterized by a DSC thermogram having a solid-solid transition endotherm with an onset in the range of about 147°C to about 157°C. For example, in some embodiments, Form I is characterized by DSC, such as Figure 2 as shown in .
[0061] Form I can also be characterized by thermogravimetric analysis (TGA). Thus, Form I can be characterized by a weight loss in the range of about 0% to about 1%, with an onset temperature in the range of about 145°C to about 150°C. For example, Form I can be characterized by a weight loss of about 0.6% up to about 200°C. In some embodiments, Form I has substantially Figure 3Thermogravimetric analysis depicted in , wherein by "substantially" it is meant that the reported TGA features may vary by about ±5°C. In embodiments, Form I has substantially Figure 4 Dynamic vapor sorption ("DVS") shown in FIG.
[0062] Free base anhydrous crystalline form II
[0063] The free base anhydrous crystalline Form II of Compound A ("Form II") can be characterized by an X-ray powder diffraction pattern obtained as described in the Examples using Cu Ka radiation with peaks at about 7.67, 11.54, 18.27, and 23.28 ± 0.2 ° 2θ. Optionally, Form II can also be characterized by an X-ray powder diffraction pattern with additional peaks at about 15.36, 16.33, 18.58, 21.38, 23.59, 24.61, 27.09, 43.40, and 44.26 ± 0.2 ° 2θ using Cu Ka radiation. Optionally, Form II can also be characterized by an X-ray powder diffraction pattern with additional peaks at about 18.01, 25.17, 38.15, and 39.26 ± 0.2 ° 2θ using Cu Ka radiation. Optionally, Form II may be characterized by an X-ray powder diffraction pattern having the peaks shown in Table 2 set forth in the Examples. In some embodiments, Form II has substantially Figure 5 The X-ray powder diffraction pattern shown in , where by "substantially" it is meant that the reported peaks may vary by about ±0.2°. It is well known in the XRPD art that while the relative peak heights in a spectrum depend on many factors, such as sample preparation and instrument geometry, the peak positions are relatively insensitive to experimental details.
[0064] A differential scanning calorimetry (DSC) thermogram of Form II is obtained as described in the Examples. The DSC curve indicates an endothermic transition at about 181°C ± 3°C. Thus, in some embodiments, Form II may be characterized by a DSC thermogram having a melting endotherm starting in the range of about 175°C to about 185°C. For example, in some embodiments, Form II is characterized by DSC, such as Figure 2 As shown in Figure 2 A mixture of Form I and Form II is present in the DSC shown in FIG.
[0065] Free base monohydrate crystalline form III
[0066] The free base monohydrate crystalline Form III of Compound A ("Form III") can be characterized by an X-ray powder diffraction pattern obtained as described in the Examples using Cu Ka radiation with peaks at about 7.31, 10.77, and 13.96 ± 0.2 ° 2θ. Optionally, Form III can also be characterized by an X-ray powder diffraction pattern with additional peaks at about 16.60, 18.56, 18.84, 19.41, 20.57, 21.61, 21.92, 22.28, 23.34, 24.23, 24.70, 25.69, and 28.87 ± 0.2 ° 2θ using Cu Ka radiation. Optionally, Form III can also be characterized by an X-ray powder diffraction pattern with additional peaks at about 7.94, 20.10, 23.88, and 28.38 ± 0.2 ° 2θ using Cu Ka radiation. Optionally, Form III may be characterized by an X-ray powder diffraction pattern having the peaks shown in Table 3 set forth in the Examples. In some embodiments, Form III has substantially Figure 6 The X-ray powder diffraction pattern shown in , wherein by "substantially" it is meant that the reported peaks may vary by about ±0.2°.
[0067] A differential scanning calorimetry (DSC) thermogram of Form III is obtained as described in the Examples. The DSC curve indicates an endothermic transition at about 132°C ± 3°C. Thus, in some embodiments, Form III may be characterized by a DSC thermogram having a melting endotherm starting in the range of about 127°C to about 137°C. For example, in some embodiments, Form III is characterized by DSC, such as Figure 7 as shown in .
[0068] Form III can also be characterized by thermogravimetric analysis (TGA). Thus, Form III can be characterized by a weight loss in the range of about 2.5% to about 3.2%, with an onset temperature in the range of about 25°C to about 35°C. For example, Form III can be characterized by a weight loss of about 2.8% up to about 200°C. In some embodiments, Form III has substantially Figure 8 Thermogravimetric analysis depicted in , wherein by "substantially" it is meant that the reported TGA features may vary by about ±5°C. In embodiments, Form III has substantially Fig. 9 Dynamic vapor sorption ("DVS") shown in FIG.
[0069] Free base anhydrous crystalline form IV
[0070] The free base anhydrous crystalline Form IV of Compound A ("Form IV") can be characterized by an X-ray powder diffraction pattern obtained as described in the Examples using Cu Ka radiation having peaks at about 8.06, 11.29, and 14.97 ± 0.2 ° 2θ. Optionally, Form IV can also be characterized by an X-ray powder diffraction pattern having additional peaks at about 17.19, 17.63, 18.39, 18.95, 19.17, 20.50, 24.87, 26.03, 26.62, 27.99, and 29.25 ± 0.2 ° 2θ using Cu Ka radiation. Optionally, Form IV may also be characterized by an X-ray powder diffraction pattern with additional peaks at approximately 12.08, 20.17, 22.37, 22.86, 25.69, 28.26, and 28.73 ± 0.2 ° 2θ using Cu Ka radiation. Optionally, Form IV may be characterized by an X-ray powder diffraction pattern with the peaks shown in Table 4 set forth in the Examples. In some embodiments, Form IV has substantially Fig.10 The X-ray powder diffraction pattern shown in , wherein by "substantially" it is meant that the reported peaks may vary by about ±0.2°.
[0071] A differential scanning calorimetry (DSC) thermogram of Form IV is obtained as described in the Examples. The DSC curve indicates an endothermic transition at about 167°C ± 3°C. Thus, in some embodiments, Form IV may be characterized by a DSC thermogram having a melting endotherm starting in the range of about 160°C to about 175°C. For example, in some embodiments, Form IV is characterized by DSC, such as Fig.11 as shown in .
[0072] Form IV can also be characterized by thermogravimetric analysis (TGA). Thus, Form IV can be characterized by a weight loss in the range of about 0% to about 0.5%, with an onset temperature in the range of about 25°C to about 35°C. For example, Form IV can be characterized by a weight loss of about 0% up to about 200°C. In some embodiments, Form IV has substantially Fig.12 Thermogravimetric analysis depicted in , wherein by "substantially" it is meant that the reported TGA features may vary by about ±5°C. In embodiments, Form IV has substantially Fig.13 Dynamic vapor sorption ("DVS") shown in FIG.
[0073] A summary of the unique XRPD peaks of the free base crystalline forms I to IV can be found in Table 5, and an overlay of the four different crystalline forms is shown in Fig.14 In. Fig.15 A description of the thermodynamic relationship between free base crystalline forms I to IV is depicted in FIG.
[0074] Compound A Salt
[0075] Crystalline hydrochloride
[0076] The crystalline form of the hydrochloride salt of Compound A ("hydrochloride salt") can be characterized by an X-ray powder diffraction pattern obtained as described in the Examples using Cu Ka radiation at about 8.45, 16.93, 23.74, 24.59, and 26.57 ± 0.2 ° 2θ with peaks. Optionally, the hydrochloride salt can also be characterized by an X-ray powder diffraction pattern having additional peaks at about 17.33, 17.76, 18.75, 19.51, 19.81, 20.53, 21.36, 22.95, 25.28, 25.89, 26.94, 27.44, and 29.41 ± 0.2 ° 2θ using Cu Ka radiation. Optionally, the hydrochloride salt may also be characterized by an X-ray powder diffraction pattern with additional peaks at about 8.74, 16.08, 19.81, and 28.58 ± 0.2 ° 2θ using Cu Ka radiation. Optionally, the hydrochloride salt may be characterized by an X-ray powder diffraction pattern with the peaks shown in Table 6 set forth in the Examples. In some embodiments, the hydrochloride salt has substantially Fig.16 The X-ray powder diffraction pattern shown in , wherein by "substantially" it is meant that the reported peaks may vary by about ±0.2°.
[0077] A differential scanning calorimetry (DSC) thermogram of the hydrochloride salt is obtained as described in the Examples. The DSC curve indicates an endothermic transition at about 134°C ± 3°C. Thus, in some embodiments, the hydrochloride salt may be characterized by a DSC thermogram having a decomposition endotherm starting in the range of about 125°C to about 140°C. For example, in some embodiments, the hydrochloride salt is characterized by DSC, such as Fig.17 as shown in .
[0078] The hydrochloride salt may also be characterized by thermogravimetric analysis (TGA). Thus, the hydrochloride salt may be characterized by a weight loss in the range of about 6.5% to about 8.5%, with an onset temperature in the range of about 25°C to about 35°C. For example, the hydrochloride salt may be characterized by a weight loss of about 7.5% up to about 200°C. In some embodiments, the hydrochloride salt has a weight loss of about 1.5%. Fig.18 Thermogravimetric analysis depicted in , wherein by "substantially" it is meant that the reported TGA features may vary by about ±5°C. In embodiments, the hydrochloride salt has substantially Fig.19 Dynamic vapor sorption ("DVS") shown in FIG.
[0079] Compound A Solvate
[0080] Dichloromethane Solvate
[0081] The crystalline form of Compound A and dichloromethane (dichloromethane solvate) can be characterized by an X-ray powder diffraction pattern obtained as described in the Examples using Cu Ka radiation at about 11.46, 16.91, 23.10, and 24.58 ± 0.2 ° 2θ with peaks. Optionally, the dichloromethane solvate can also be characterized by an X-ray powder diffraction pattern having additional peaks at about 8.25, 16.26, 18.82, 19.50, 19.90, 20.52, 20.79, 21.58, 23.92, and 29.35 ± 0.2 ° 2θ using Cu Ka radiation. Optionally, the dichloromethane solvate may be further characterized by an X-ray powder diffraction pattern with additional peaks at about 6.76, 25.18, 26.20, 26.95, 27.18, 27.62, and 28.26 ± 0.2 ° 2θ using Cu Kα radiation. Optionally, the dichloromethane solvate may be characterized by an X-ray powder diffraction pattern with the peaks shown in Table 7 set forth in the Examples. In some embodiments, the dichloromethane solvate has substantially Fig. 20 The X-ray powder diffraction pattern shown in , wherein by "substantially" it is meant that the reported peaks may vary by about ±0.2°.
[0082] A differential scanning calorimetry (DSC) thermogram of a dichloromethane solvate is obtained as described in the Examples. The DSC curve indicates an endothermic transition at about 76°C ± 3°C. Thus, in some embodiments, a dichloromethane solvate may be characterized by a DSC thermogram having a desolvation endotherm starting in the range of about 70°C to about 80°C. For example, in some embodiments, a dichloromethane solvate is characterized by DSC, such as Fig.21 as shown in .
[0083] The dichloromethane solvate may also be characterized by thermogravimetric analysis (TGA). Thus, the dichloromethane solvate may be characterized by a weight loss in the range of about 10% to about 12%, with an onset temperature in the range of about 65°C to about 85°C. For example, the dichloromethane solvate may be characterized by a weight loss of about 10.9% up to about 200°C. In some embodiments, the dichloromethane solvate has a weight loss of about 10.9%. Fig. 22 Thermogravimetric analysis depicted in , where by "substantially" it is meant that the reported TGA features may vary by about ±5°C.
[0084] Nitromethane Solvate
[0085] The crystalline form of Compound A and nitromethane ("nitromethane solvate") may be characterized by an X-ray powder diffraction pattern obtained as described in the Examples using Cu Ka radiation with peaks at about 8.94, 15.86, 17.12, 19.51, 19.83, and 24.41 ± 0.2 ° 2θ. Optionally, the nitromethane solvate may also be characterized by an X-ray powder diffraction pattern using Cu Ka radiation with additional peaks at about 10.18, 18.16, 20.54, 21.93, 23.06, 23.92, and 25.37 ± 0.2 ° 2θ. Optionally, the nitromethane solvate may also be characterized by an X-ray powder diffraction pattern using Cu Ka radiation with additional peaks at about 19.01, 22.68, 26.61, and 28.32 ± 0.2 ° 2θ. Optionally, the nitromethane solvate may be characterized by an X-ray powder diffraction pattern having the peaks shown in Table 8 set forth in the Examples. In some embodiments, the nitromethane solvate has substantially Fig.23 The X-ray powder diffraction pattern shown in , wherein by "substantially" it is meant that the reported peaks may vary by about ±0.2°.
[0086] A differential scanning calorimetry (DSC) thermogram of a nitromethane solvate is obtained as described in the Examples. The DSC curve indicates an endothermic transition at about 89°C ± 3°C. Thus, in some embodiments, a nitromethane solvate may be characterized by a DSC thermogram having a desolvation endotherm starting in the range of about 81°C to about 97°C. For example, in some embodiments, a nitromethane solvate is characterized by DSC, such as Fig.24 as shown in .
[0087] The nitromethane solvate may also be characterized by thermogravimetric analysis (TGA). Thus, the nitromethane solvate may be characterized by a weight loss in the range of about 6% to about 7%, with an onset temperature in the range of about 60°C to about 80°C. For example, the nitromethane solvate may be characterized by a weight loss of about 6.5% up to about 200°C. In some embodiments, the nitromethane solvate has a weight loss of about 1.5%. Fig.25 Thermogravimetric analysis depicted in , where by "substantially" it is meant that the reported TGA features may vary by about ±5°C.
[0088] Hexafluoro-2-propanol solvate
[0089] Compound A and a crystalline form of hexafluoro-2-propanol ("hexafluoro-2-propanol solvate") may be characterized by an X-ray powder diffraction pattern obtained as described in the Examples using Cu Kα radiation having peaks at about 16.17, 16.70, 18.20, and 23.03 ± 0.2° 2θ. Optionally, the hexafluoro-2-propanol solvate may also be characterized by an X-ray powder diffraction pattern having additional peaks at about 9.49, 11.20, 20.18, 21.39 23.74, 25.46, 27.00, 29.24, and 33.76 ± 0.2° 2θ using CuKα radiation. Optionally, the hexafluoro-2-propanol solvate may be characterized by an X-ray powder diffraction pattern having the peaks shown in Table 9 described in the Examples. In some embodiments, the hexafluoro-2-propanol solvate has substantially Fig.26 The X-ray powder diffraction pattern shown in , wherein by "substantially" it is meant that the reported peaks may vary by about ±0.2°.
[0090] A differential scanning calorimetry (DSC) thermogram of the hexafluoro-2-propanol solvate is obtained as described in the Examples. The DSC curve indicates an endothermic transition at about 90°C ± 3°C. Thus, in some embodiments, the hexafluoro-2-propanol solvate may be characterized by a DSC thermogram having a decomposition endotherm starting in the range of about 85°C to about 95°C. For example, in some embodiments, the hexafluoro-2-propanol solvate is characterized by DSC, such as Fig. 27 as shown in .
[0091] The hexafluoro-2-propanol solvate can also be characterized by thermogravimetric analysis (TGA). Thus, the hexafluoro-2-propanol solvate can be characterized by a weight loss in the range of about 9.4% to about 10.4%, with an onset temperature in the range of about 75° C. to about 85° C. For example, the hexafluoro-2-propanol solvate can be characterized by a weight loss of about 9.9% up to about 200° C. In some embodiments, the hexafluoro-2-propanol solvate has a weight loss of about 1.5 % and a weight loss of about 2.5 % at about 1.5 % and ... Fig.28 Thermogravimetric analysis depicted in , where by "substantially" it is meant that the reported TGA features may vary by about ±5°C.
[0092] Compound A co-crystal
[0093] Provided herein are co-crystals of Compound A with various coformers. The co-crystal comprises Compound A hydrogen bonded to the coformer. In embodiments, the co-crystal may comprise Compound A and the coformer in a molar ratio of 10:1 to 1:10 or 5:1 to 1:5. For example, the co-crystal may comprise Compound A and the coformer in a molar ratio of about 2:1, about 1:1, about 1:1.5, about 1:2, about 1:2.5, about 1:3, about 1:3.5, about 1:4, or about 1:5.
[0094] In embodiments, the coformer may include benzoic acid, oxalic acid, malonic acid, succinic acid, maleic acid, fumaric acid, glutaric acid, adipic acid, pimelic acid, 3,5-dihydroxybenzoic acid, trifluoroacetic acid, 2,5-dihydroxybenzoic acid, 2,4-dihydroxybenzoic acid, m-nitrobenzoic acid, 5-chlorosalicylic acid, saccharin, citric acid, tartaric acid, 2,3-dihydroxybenzoic acid, 3,4-dihydroxybenzoic acid, barbital, 4-hydroxybenzoic acid, 1-hydroxy-2-naphthoic acid, malic acid, 3-hydroxybenzoic acid , 6-hydroxy-2-naphthoic acid, methyl gallate, salicylic acid, 2-hydroxybenzoic acid, formic acid, 3-hydroxy-2-naphthoic acid, sulfoacetamide, acetic acid, sulfaproxyline, sulfuric acid, aminosulfonic acid, ethylenediamine, octadecylamine, glucono-delta lactone, allocitric acid, sucralose, indole, 1-hydroxyethylidene-1,1-diphosphonic acid, skatole, 5-chlorosalicylic acid, urea, 5-nitroisophthalic acid, trimesic acid, gentisic acid Acid, ketoglutaric acid, adamantanetricarboxylic acid, tert-butylhydroquinone, isocitric acid, trifluoroethanol, camphoric acid, 4-aminobenzoic acid, 2,6-pyridinedicarboxylic acid, aspirin, butyric acid, formamide, nicotinamide, nitromethane, 1,4-benzoquinone, glycolic acid, terephthalaldehyde, dioxane, N-methylpyrrolidone, dimethylsulfoxide, dimethylacetamide, acetone, dimethylformamide, furfural, 4,4'-bipyridine, or mixtures thereof. In embodiments, the coformer may include propyl gallate, glycerol, propylene glycol, maltol, urea, or mixtures thereof.
[0095] In embodiments, the co-crystals herein may further comprise a co-crystallization solvent. The co-crystallization solvent is the solvent from which the co-crystal occurs. The co-crystallization solvent may include an organic solvent that can be used in crystallization. Such organic solvents are known to those skilled in the art. In embodiments, the co-crystallization solvent may be ethyl acetate or acetone.
[0096] Propyl Gallate Cocrystal
[0097] Provided herein are co-crystals of Compound A and propyl gallate. Co-crystals of Compound A and propyl gallate ("propyl gallate co-crystals") may be characterized in that, when using Cu Kα radiation, an X-ray powder diffraction pattern obtained as described in the Examples has peaks at about 8.66, 15.00, 17.72, 18.82, and 20.32 ± 0.2 ° 2θ. Optionally, the propyl gallate co-crystal may also be characterized in that, when using Cu Kα radiation, an X-ray powder diffraction pattern has additional peaks at about 9.21, 19.36, 20.49, and 22.57 ± 0.2 ° 2θ. Optionally, the propyl gallate co-crystals may be further characterized by an X-ray powder diffraction pattern having additional peaks at about 3.05, 11.24, 18.32, 21.73, 22.98, 23.39, 25.01, 25.51, 26.30, 26.52, and 28.31 ± 0.2° 2θ using Cu Ka radiation. Optionally, the propyl gallate co-crystals may be characterized by an X-ray powder diffraction pattern having the peaks shown in Table 10 set forth in the Examples. In some embodiments, the propyl gallate co-crystals have substantially Fig.29 The X-ray powder diffraction pattern shown in , wherein by "substantially" it is meant that the reported peaks may vary by about ±0.2°.
[0098] A differential scanning calorimetry (DSC) thermogram of propyl gallate co-crystals was obtained as described in the Examples. The DSC curve indicates an endothermic transition at about 121°C ± 3°C. Thus, in some embodiments, the propyl gallate co-crystals may be characterized by a DSC thermogram having a melting endotherm starting in the range of about 116°C to about 126°C. For example, in some embodiments, the propyl gallate co-crystals are characterized by DSC, such as Fig.30 as shown in .
[0099] The propyl gallate co-crystals may also be characterized by thermogravimetric analysis (TGA). Thus, the propyl gallate co-crystals may be characterized by a weight loss in the range of about 25% to about 35%, with an onset temperature in the range of about 190° C. to about 210° C. For example, the propyl gallate co-crystals may be characterized by a weight loss of about 29.9% up to about 260° C. In some embodiments, the propyl gallate co-crystals have a weight loss of about 29.9%. Fig.31 Thermogravimetric analysis depicted in , where by "substantially" it is meant that the reported TGA features may vary by about ±5°C.
[0100] Glycerol eutectic
[0101] Provided herein are co-crystals of Compound A and glycerol. Co-crystals of Compound A and glycerol ("glycerol co-crystals") may be characterized by an X-ray powder diffraction pattern obtained as described in the Examples using Cu Ka radiation having peaks at about 16.84, 18.48, 19.40, and 21.49 ± 0.2 ° 2θ. Optionally, the glycerol co-crystal may also be characterized by an X-ray powder diffraction pattern having additional peaks at about 9.70, 15.60, 16.39, 18.95, 22.51, 24.53, and 24.92 ± 0.2 ° 2θ using Cu Ka radiation. Optionally, the glycerol co-crystal may also be characterized by an X-ray powder diffraction pattern having additional peaks at about 8.17, 12.38, 22.87, and 27.61 ± 0.2 ° 2θ using Cu Ka radiation. Optionally, the glycerol co-crystal may be characterized by an X-ray powder diffraction pattern having the peaks shown in Table 11 set forth in the Examples. In some embodiments, the glycerol co-crystal has substantially Fig.32 The X-ray powder diffraction pattern shown in , wherein by "substantially" it is meant that the reported peaks may vary by about ±0.2°.
[0102] A differential scanning calorimetry (DSC) thermogram of the glycerol co-crystal is obtained as described in the Examples. The DSC curve indicates endothermic transitions at about 148°C ± 3°C and 156°C ± 3°C. Thus, in some embodiments, the glycerol co-crystal may be characterized by a DSC thermogram having a decomposition endotherm with an onset in the range of about 140°C to about 151°C and about 152°C to 165°C. For example, in some embodiments, the glycerol co-crystal is characterized by DSC, such as Fig.33 as shown in .
[0103] The glycerol co-crystals may also be characterized by thermogravimetric analysis (TGA). Thus, the glycerol co-crystals may be characterized by a weight loss in the range of about 20% to about 35%, with an onset temperature in the range of about 25°C to about 35°C. For example, the glycerol co-crystals may be characterized by a weight loss of about 30.5% up to about 250°C. In some embodiments, the glycerol co-crystals have a weight loss of about 1.5 %. Fig.34 Thermogravimetric analysis depicted in , where by "substantially" it is meant that the reported TGA features may vary by about ±5°C.
[0104] Propylene glycol eutectic
[0105] Provided herein are co-crystals of Compound A and propylene glycol. Co-crystals of Compound A and propylene glycol ("propylene glycol co-crystals") may be characterized by an X-ray powder diffraction pattern obtained as described in the Examples using Cu Kα radiation at about 16.82, 18.26, 18.93, 19.37, and 21.52 ± 0.2 ° 2θ having peaks. Optionally, the propylene glycol co-crystal may also be characterized by an X-ray powder diffraction pattern having additional peaks at about 7.87, 15.61, 16.36, 18.39, 20.39, 21.12, 22.47, and 24.46 ± 0.2 ° 2θ using Cu Kα radiation. Optionally, the propylene glycol co-crystal may be further characterized by an X-ray powder diffraction pattern having additional peaks at about 9.69, 20.02, 21.83, 22.85, 23.84, 25.05, and 27.07 ± 0.2° 2θ using Cu Ka radiation. Optionally, the propylene glycol co-crystal may be characterized by an X-ray powder diffraction pattern having the peaks shown in Table 12 set forth in the Examples. In some embodiments, the propylene glycol co-crystal has substantially Fig.35 The X-ray powder diffraction pattern shown in , wherein by "substantially" it is meant that the reported peaks may vary by about ±0.2°.
[0106] A differential scanning calorimetry (DSC) thermogram of the propylene glycol co-crystal is obtained as described in the Examples. The DSC curve indicates a broad endothermic transition at about 89°C ± 3°C to 124°C ± 3°C. Thus, in some embodiments, the propylene glycol co-crystal may be characterized by a DSC thermogram having a decomposition endotherm with an onset in the range of about 80°C to about 135°C. For example, in some embodiments, the propylene glycol co-crystal is characterized by DSC, such as Fig.36 as shown in .
[0107] The propylene glycol co-crystals may also be characterized by thermogravimetric analysis (TGA). Thus, the propylene glycol co-crystals may be characterized by a weight loss in the range of about 5.5% to about 8%, with an onset temperature in the range of about 30° C. to about 50° C. For example, the propylene glycol co-crystals may be characterized by a weight loss of about 7.3% up to about 200° C. In some embodiments, the propylene glycol co-crystals have a weight loss of about 1.5% to about 2.0%. Fig.37 Thermogravimetric analysis depicted in , where by "substantially" it is meant that the reported TGA features may vary by about ±5°C.
[0108] Maltol eutectic
[0109] Provided herein are co-crystals of Compound A and maltol. Co-crystals of Compound A and maltol ("maltol co-crystals") may be characterized in that, when using Cu Kα radiation, the X-ray powder diffraction pattern obtained as described in the Examples has peaks at about 16.85, 18.18, 19.53, and 23.54 ± 0.2 ° 2θ. Optionally, the maltol co-crystal may also be characterized in that, when using Cu Kα radiation, the X-ray powder diffraction pattern has additional peaks at about 6.58, 8.86, 13.68, 14.60, 15.25, 21.52, 25.26, and 26.63 ± 0.2 ° 2θ. Optionally, the maltol co-crystal may also be characterized in that, when using Cu Kα radiation, the X-ray powder diffraction pattern has additional peaks at about 4.44, 7.98, and 13.13 ± 0.2 ° 2θ. Optionally, the maltol co-crystals may be characterized by an X-ray powder diffraction pattern having the peaks shown in Table 13 set forth in the Examples. In some embodiments, the maltol co-crystals have substantially Fig.38 The X-ray powder diffraction pattern shown in , wherein by "substantially" it is meant that the reported peaks may vary by about ±0.2°.
[0110] A differential scanning calorimetry (DSC) thermogram of the maltol co-crystal is obtained as described in the Examples. The DSC curve indicates a broad endothermic transition at about 130°C ± 3°C. Thus, in some embodiments, the maltol co-crystal may be characterized by a DSC thermogram having a decomposition endotherm starting in the range of about 125°C to about 135°C. For example, in some embodiments, the maltol co-crystal is characterized by DSC, such as Fig.39 as shown in .
[0111] The maltol co-crystals may also be characterized by thermogravimetric analysis (TGA). Thus, the maltol co-crystals may be characterized by a weight loss in the range of about 1% to about 2.5%, with an onset temperature in the range of about 60°C to about 80°C. For example, the maltol co-crystals may be characterized by a weight loss of about 1.5% up to about 200°C. In some embodiments, the maltol co-crystals have a weight loss of about 1.5%. Fig.40 Thermogravimetric analysis depicted in , where by "substantially" it is meant that the reported TGA features may vary by about ±5°C.
[0112] Urea eutectic
[0113] Provided herein are co-crystals of Compound A and urea. Co-crystals of Compound A and urea ("urea co-crystals") may be characterized by an X-ray powder diffraction pattern obtained as described in the Examples using Cu Kα radiation at about 3.99, 11.24, 17.62, and 18.37 ± 0.2 ° 2θ having peaks. Optionally, the urea co-crystal may also be characterized by an X-ray powder diffraction pattern having additional peaks at about 8.01, 8.39, 14.96, 17.47, 18.94, 19.13, 20.51, 24.65, 24.86, 25.70, 25.97, and 26.62 ± 0.2 ° 2θ using Cu Kα radiation. Optionally, the urea co-crystal may be further characterized by an X-ray powder diffraction pattern with additional peaks at about 15.21, 16.93, 17.16, 22.37, 26.35, 28.01, 28.26, 28.77, and 29.25 ± 0.2° 2θ using Cu Ka radiation. Optionally, the urea co-crystal may be characterized by an X-ray powder diffraction pattern with the peaks shown in Table 14 set forth in the Examples. In some embodiments, the urea co-crystal has substantially Fig.41 The X-ray powder diffraction pattern shown in , wherein by "substantially" it is meant that the reported peaks may vary by about ±0.2°.
[0114] A differential scanning calorimetry (DSC) thermogram of the urea co-crystal is obtained as described in the Examples. The DSC curve indicates broad endothermic transitions at about 167°C ± 3°C and 174°C ± 3°C. Thus, in some embodiments, the urea co-crystal may be characterized by a DSC thermogram having a decomposition endotherm with an onset in the range of about 160°C to about 170°C and about 171°C to about 180°C. For example, in some embodiments, the urea co-crystal is characterized by DSC, such as Fig.42 as shown in .
[0115] The urea co-crystals may also be characterized by thermogravimetric analysis (TGA). Thus, the urea co-crystals may be characterized by a weight loss in the range of about 9.6% to about 11.6%, with an onset temperature in the range of about 145° C. to about 165° C. For example, the urea co-crystals may be characterized by a weight loss of about 10.6% up to about 225° C. In some embodiments, the urea co-crystals have a weight loss of about 10.6%. Fig.43 Thermogravimetric analysis depicted in , where by "substantially" it is meant that the reported TGA features may vary by about ±5°C.
[0116] Amorphous form
[0117] Provided herein is an amorphous form of Compound A. In some embodiments, the amorphous form of Compound A has substantially Fig.44The X-ray powder diffraction pattern shown in , wherein by "substantially" it is meant that the reported peaks may vary by about ±0.2°.
[0118] The amorphous form of Compound A can also be characterized by thermogravimetric analysis (TGA). Thus, the amorphous form of Compound A can be characterized by a weight loss in the range of about 2% to about 4%, with an onset temperature in the range of about 25° C. to about 55° C. For example, the urea co-crystal can be characterized by a weight loss of about 2.9% up to about 150° C. In some embodiments, the amorphous form has substantially Fig.45 Thermogravimetric analysis depicted in , where by "substantially" it is meant that the reported TGA features may vary by about ±5°C.
[0119] Pharmaceutical composition
[0120] Also provided herein are pharmaceutical compositions comprising a crystalline form and / or co-crystal of Compound A or a salt thereof as described herein; and a pharmaceutically acceptable carrier. In an embodiment, the carrier may include an excipient.
[0121] The phrase "pharmaceutically acceptable" is used herein to refer to those ligands, materials, compositions and / or dosage forms that are suitable for use in contact with the tissues of humans and animals without excessive toxicity, irritation, allergic response, or other problems or complications, commensurate with a reasonable benefit / risk ratio, within the scope of sound medical judgment. The compositions described herein can be formulated for any form of administration. In various cases, the compositions are for oral administration. In various cases, the compositions are in tablet form.
[0122] As used herein, the phrase "pharmaceutically acceptable carrier" means a pharmaceutically acceptable material, composition or vehicle, such as a liquid or solid filler, diluent, excipient, solvent or encapsulating material. As used herein, the phrase "pharmaceutically acceptable carrier" includes buffers, sterile water for injection, solvents, dispersion media, coatings, antibacterial and antifungal agents, isotonic agents and absorption delaying agents, etc., which are compatible with drug administration. Each carrier must be "acceptable" in the sense of being compatible with the other ingredients of the formulation and not harmful to the patient. Some examples of materials that can serve as pharmaceutically acceptable carriers include: (1) sugars such as lactose, glucose, and sucrose; (2) starches such as corn starch, potato starch, and substituted or unsubstituted β-cyclodextrins; (3) cellulose and its derivatives such as sodium carboxymethylcellulose, ethylcellulose, and cellulose acetate; (4) powdered tragacanth; (5) malt; (6) gelatin; (7) talc; (8) excipients such as cocoa butter and suppository waxes; (9) oils such as Such as peanut oil, cottonseed oil, safflower oil, sesame oil, olive oil, corn oil and soybean oil; (10) glycols, such as propylene glycol; (11) polyols, such as glycerol, sorbitol, mannitol and polyethylene glycol; (12) esters, such as ethyl oleate and ethyl laurate; (13) agar; (14) buffers, such as magnesium hydroxide and aluminum hydroxide; (15) alginic acid; (16) pyrogen-free water; (17) isotonic saline; (18) Ringer's solution; (19) ethanol; (20) phosphate buffer solution; and (21) other non-toxic compatible substances used in pharmaceutical preparations. In certain embodiments, the pharmaceutical compositions provided herein are pyrogen-free, i.e., do not induce a significant temperature increase when administered to a patient.
[0123] Wetting agents, emulsifiers and lubricants, such as sodium lauryl sulfate and magnesium stearate, as well as coloring agents, release agents, coating agents, sweetening, flavoring and perfuming agents, preservatives and antioxidants can also be present in the composition as excipients.
[0124] Examples of pharmaceutically acceptable antioxidants as excipients include: (1) water-soluble antioxidants, such as ascorbic acid, cysteine hydrochloride, sodium bisulfate, sodium metabisulfite, sodium sulfite, etc.; (2) oil-soluble antioxidants, such as ascorbyl palmitate, butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT), lecithin, propyl gallate, α-tocopherol, etc.; and (3) metal chelators, such as citric acid, ethylenediaminetetraacetic acid (EDTA), sorbitol, tartaric acid, phosphoric acid, etc.
[0125] The pharmaceutical composition may also contain adjuvants, such as preservatives, wetting agents, emulsifiers and dispersants. Prevention of microbial action may be ensured by including various antibacterial and antifungal agents such as parabens, chlorobutanol, phenol, sorbic acid, etc. It may also be desirable to include tonicity modifiers such as sugars, etc. in the composition. In addition, extended absorption of injectable drug forms may be achieved by including agents that delay absorption such as aluminum monostearate and gelatin.
[0126] In some cases, to prolong the effect of one or more compounds provided herein, it may be desirable to slow the absorption of the compound from subcutaneous or intramuscular injection. For example, delayed absorption of a parenterally administered compound can be achieved by dissolving or suspending the compound in an oil vehicle.
[0127] The composition should be stable under the conditions of manufacture and storage and must be preserved against the contaminating action of microorganisms such as bacteria and fungi. Prevention of the action of microorganisms can be achieved by various antibacterial and antifungal agents such as parabens, chlorobutanol, phenol, ascorbic acid, thimerosal, and the like. In many cases, it will be preferred to include isotonic agents such as sugars; polyols such as mannitol, sorbitol; and sodium chloride in the composition. Prolonged absorption of injectable compositions can be achieved by including agents that delay absorption in the composition such as aluminum monostearate and gelatin.
[0128] Sterile injectable solutions can be prepared by incorporating the active compound in the desired amount into an appropriate solvent together with one or a combination of ingredients listed above as desired, followed by filtration sterilization. Typically, dispersions are prepared by incorporating the active compound into a sterile vehicle containing a basic dispersion medium and other ingredients required from the ingredients listed above. In the case of sterile powders for the preparation of sterile injectable solutions, the preparation method is freeze drying (lyophilization), which produces a powder of the active ingredient plus any additional required ingredients from its previously sterile filtered solution.
[0129] Injectable reservoir forms can be prepared by forming a microcapsule or nanocapsule matrix of the compound provided herein in a biodegradable polymer such as polylactide-polyglycolide. Depending on the ratio of the drug to the polymer and the properties of the specific polymer used, the rate of drug release can be controlled. Examples of other biodegradable polymers include poly(orthoesters) and poly(anhydrides). Reservoir injectable formulations are also prepared by encapsulating the drug in liposomes, microemulsions or nanoemulsions that are compatible with body tissues.
[0130] In some embodiments, the polymorphs and salts disclosed herein are prepared with carriers that will protect the therapeutic compound from rapid elimination from the body, such as controlled release formulations, including implants and microencapsulation delivery systems. Biodegradable biocompatible polymers such as ethylene vinyl acetate, polyanhydrides, polyglycolic acid, collagen, polyorthoesters, and polylactic acid can be used. Such preparations can be prepared using standard techniques, or commercially available, for example, from Alza Corporation and Nova Pharmaceuticals, Inc. Liposomal suspensions (including liposomes targeted to selected cells with monoclonal antibodies to cellular antigens) can also be used as pharmaceutically acceptable carriers. These liposomal suspensions can be prepared according to methods known to those skilled in the art, such as described in U.S. Patent No. 4,522,811, which is incorporated herein by reference in its entirety.
[0131] The pharmaceutical compositions can be included in a container, pack, or dispenser together with instructions for administration.
[0132] How to use
[0133] Compound A or its salt form or co-crystal disclosed herein or the pharmaceutical composition described herein can be used to treat or prevent heart failure, including but not limited to: acute (or decompensated) congestive heart failure and chronic congestive heart failure; in particular, diseases associated with abnormal systolic heart function.
[0134] Also provided herein is a method for treating or preventing heart failure in a subject in need thereof, the method comprising administering to the subject one or more of the forms or co-crystals of Compound A or its salts disclosed herein, or one or more of the pharmaceutical compositions described herein, in an amount effective to treat or prevent heart failure. Also provided is a method for treating or preventing heart failure using the disclosed forms or co-crystals of Compound A or its salts or compositions thereof, including but not limited to: acute (or decompensated) congestive heart failure and chronic congestive heart failure.
[0135] Also provided herein is the use of a form of Compound A or a salt thereof or a co-crystal disclosed herein or a pharmaceutical composition described herein for the manufacture of a medicament for treating or preventing heart failure. In some embodiments, the present disclosure provides the use of a form of Compound A or a salt thereof or a co-crystal disclosed herein or a pharmaceutical composition described herein for the manufacture of a medicament for treating acute (or decompensated) congestive heart failure and chronic congestive heart failure.
[0136] In some embodiments, a form of Compound A or a salt thereof or a co-crystal disclosed herein is used to treat or prevent heart failure with reduced ejection fraction (HFrEF) or systolic heart failure, dilated cardiomyopathy, postpartum cardiomyopathy, idiopathic cardiomyopathy, pediatric HFrEF, chemotherapy-induced heart failure, heart failure associated with muscular dystrophy, biventricular HFrEF, HFrEF with pulmonary hypertension, heart failure with preserved ejection fraction (HFpEF) with right ventricular dysfunction, pulmonary hypertension with right ventricular dysfunction, scleroderma with pulmonary hypertension, right ventricular dysfunction, Chagas disease, or myocarditis. In some embodiments, provided herein is a method for treating or preventing heart failure with reduced ejection fraction or systolic heart failure, dilated cardiomyopathy, postpartum cardiomyopathy, idiopathic cardiomyopathy, pediatric HFrEF, chemotherapy-induced heart failure, heart failure associated with muscular dystrophy, biventricular HFrEF, HFrEF with pulmonary hypertension, heart failure with preserved ejection fraction (HFpEF) with right ventricular dysfunction, pulmonary hypertension with right ventricular dysfunction, scleroderma with pulmonary hypertension, right ventricular dysfunction, Chagas disease, or myocarditis, the method comprising administering to a subject in need thereof an effective amount of one or more forms or co-crystals of Compound A or a salt thereof disclosed herein. Also provided herein is the use of one or more forms or co-crystals of Compound A or its salt disclosed herein for the manufacture of a medicament for treating or preventing heart failure with reduced ejection fraction or systolic heart failure, dilated cardiomyopathy, postpartum cardiomyopathy, idiopathic cardiomyopathy, pediatric HFrEF, chemotherapy-induced heart failure, heart failure associated with muscular dystrophy, biventricular HFrEF, HFrEF with pulmonary hypertension, heart failure with preserved ejection fraction (HFpEF) with right ventricular dysfunction, pulmonary hypertension with right ventricular dysfunction, scleroderma with pulmonary hypertension, right ventricular dysfunction, Chagas disease, or myocarditis.
[0137] In some embodiments, the dilated cardiomyopathy is selected from the group consisting of: hereditary dilated cardiomyopathy, peripartum cardiomyopathy (e.g., postpartum cardiomyopathy), idiopathic dilated cardiomyopathy, post-infectious dilated cardiomyopathy, toxin-induced dilated cardiomyopathy, and nutritional deficiency dilated cardiomyopathy. In some embodiments, pediatric HFrEF occurs in pediatric patients with univentricular hearts or single ventricles or patients following Fontan or Fontan-Kreutzer procedures. In some embodiments, pediatric HFrEF is pediatric heart failure associated with congenital heart disease. In some embodiments, chemotherapy-induced heart failure is selected from the group consisting of chemotherapy-induced left ventricular dysfunction, radiation-induced heart failure, heart failure caused by anthracycline treatment (including but not limited to doxorubicin, epirubicin and daunorubicin), heart failure caused by anti-ERBB2 treatment (including but not limited to trastuzumab and lapatinib), heart failure caused by VEGF inhibitor treatment (including but not limited to bevacizumab), and heart failure caused by tyrosine kinase inhibitor treatment (including but not limited to imatinib, dasatinib, nilotinim, sorafenib and sunitinib). In some embodiments, the heart failure associated with muscular dystrophy is selected from the group consisting of heart failure associated with Duchenne muscular dystrophy, heart failure associated with Becker muscular dystrophy, heart failure associated with myotonic dystrophy (e.g., Steinert's disease), heart failure associated with laminopathy, such as Emery-Dreifuss muscular dystrophy (EDMD), including both X-linked EDMD and autosomal dominant EDMD, heart failure associated with facioscapulohumeral muscular dystrophy (FSHMD), heart failure associated with limb-girdle muscular dystrophy, including sarcoglycanopathy and autosomal dominant forms of the disease, and heart failure associated with congenital muscular dystrophy.In some embodiments, pulmonary hypertension with right ventricular dysfunction is associated with high left ventricular (diastolic) pressure in HFrEF or high left ventricular (diastolic) pressure in HFpEF.
[0138] "Treatment / treating" includes one or more of the following: a) inhibiting a disease or condition; b) slowing or arresting the development of clinical symptoms of a disease or condition; and / or c) alleviating a disease or condition, i.e., causing regression of clinical symptoms. The term encompasses both complete and partial alleviation of a disease or condition and complete or partial alleviation of clinical symptoms of a disease or condition. Therefore, the forms or co-crystals of Compound A or its salts described herein or the pharmaceutical compositions described herein can prevent the exacerbation of existing diseases or conditions, help manage the disease or condition, or alleviate or eliminate the disease or condition. "Prevention", i.e., causing clinical symptoms of a disease or condition not to manifest, includes the prophylactic administration of the pharmaceutical formulations described herein to subjects (i.e., animals, preferably mammals, most preferably humans) who are believed to be in need of preventive treatment such as chronic heart failure.
[0139] Example
[0140] method
[0141] X-ray powder diffraction (XRPD)
[0142] X-ray powder diffraction (XRPD) data were obtained using a PANalytical X'Pert PRO diffractometer. The samples were irradiated with CuKα radiation at ambient temperature. The samples were scanned in a continuous mode of 5-30 or 5-45 degrees (2θ) at 45 kV and 40 mA with a step size of 0.0334 degrees. The incident light path was equipped with a 0.02 radian Soller slit, a 15 mm mask, a 4-degree fixed anti-scatter slit, and a programmable divergence slit. The diffracted beam was equipped with a 0.02 radian Soller slit, a programmable anti-scatter slit, and a 0.02 mm nickel filter. The samples were prepared on a low background sample holder and placed on a rotating stage with a rotation time of 2 s.
[0143] Optionally, X-ray powder diffraction (XRPD) data were obtained using a PANalytical Empyrean diffractometer. The sample was scanned in continuous mode from 2.5 to 32 degrees (2θ) at 35 kV and 30 mA with a step size of 0.0131 degrees.
[0144] Differential Scanning Calorimetry (DSC)
[0145] Differential Scanning Calorimetry (DSC) analyses were performed on a TA Instruments Discovery Series calorimeter at 10°C / min from 30 to 250 degrees Celsius in a crimped aluminum pan under 50 ml / min of dry nitrogen.
[0146] Thermogravimetric analysis (TGA)
[0147] Thermogravimetric analysis (TGA) was performed on a TA Instruments Discovery Series analyzer at 10°C / min from ambient temperature to 250°C in platinum pans under 25 ml / min of dry nitrogen.
[0148] Optionally, thermogravimetric analysis (TGA) is performed on a TA Instruments thermogravimetric analyzer at 10°C / min from ambient temperature to 350°C in a platinum pan under 25 ml / min of dry nitrogen.
[0149] Moisture adsorption
[0150] A dynamic vapor sorption (DVS) analyzer was used to collect moisture sorption data. Sample amounts of approximately 5-10 mg were used in a quartz pan. Hygroscopicity was evaluated from 0 to 95% RH in increments of 5 or 10% RH. Data for adsorption and desorption cycles were collected. The equilibrium criterion was set to a weight change of 0.002% in 5 minutes, and the maximum equilibrium time was 120 minutes.
[0151] Solubility
[0152] Water: Add excess solid to water to create a suspension and disperse at room temperature for at least 24 hours. Filter the suspension. Analyze the filtrate by UPLC-UV and compare to a standard curve to determine the solution concentration of the crystalline form. Analyze the solid by XRPD to determine the crystalline form.
[0153] Toluene and propanol: Add excess solids to produce a suspension and disperse at 25, 35 and 45°C for at least 24 hours. Filter the suspension. Analyze the filtrate by UPLC-UV and compare to a standard curve to determine the solution concentration of the crystalline form. Analyze the solid by XRPD to determine the crystalline form.
[0154] Co-slurry
[0155] Excess solid Form I, Form III, and Form IV were added to water or 80% acetonitrile in water and dispersed at 25 or 50° C. for at least 24 hours. The suspension was filtered. The solids were analyzed by XRPD to determine the crystalline form.
[0156] Solid stability
[0157] The drug substance was stored at 25°C / 60%RH, 40°C / 75%RH, 40°C / ambient, or 60°C / ambient. Chemical stability at each time point was determined by dissolving the drug substance in 50% acetonitrile in water for UPLC analysis. Physical stability was determined by analysis of the solids by XRPD, DSC, and TGA.
[0158] Free base crystalline Form I: Form I was initially prepared by precipitation from 30% hydroxypropyl-β-cyclodextrin in deionized ("DI") water during formulation screening. Form I undergoes a solid-solid transition to Form II at about 150-152°C. Form I is non-hygroscopic, and the solubility of Form I in water is 0.013 mg / mL. Form I is physically and chemically stable for 14 weeks when stored at 25°C / 60%RH, 40°C / 75%RH, 40°C / ambient, or 60°C / ambient conditions.
[0159] The free base crystalline Form I is characterized by an XRPD pattern comprising the peaks in Table 1.
[0160] Table 1
[0161]
[0162]
[0163] Free base crystalline Form II: Form II is prepared by heating Form I to 150-152°C. The melting point of Form II is about 180-182°C (see DSC of Form I). Form II converts back to Form I at temperatures below 132°C.
[0164] The free base crystalline Form II is characterized by an XRPD pattern comprising the peaks in Table 2.
[0165] Table 2
[0166]
[0167]
[0168] Free base crystalline Form III: Form III was prepared by precipitation from acetonitrile (100 mg / mL) and water (1:2) at 25° C. during a solvent solubility screen. The monohydrate was dehydrated under vacuum at ambient temperature, at temperatures greater than 25° C., or in low humidity.
[0169] The free base crystalline Form III is characterized by an XRPD pattern comprising the peaks in Table 3.
[0170] Table 3
[0171]
[0172]
[0173] Free base crystalline Form IV: Form IV was initially prepared by pulling air through the Form III solid on a filter for 30 minutes at ambient conditions to dehydrate Form III. The melting point of Form IV is about 167°C. Form IV is non-hygroscopic and has a solubility of 0.010 mg / mL in water. Form IV was physically and chemically stable for 13 weeks when stored at 25°C / 60%RH, 40°C / 75%RH, 40°C / ambient, or 60°C / ambient conditions.
[0174] The free base crystalline Form IV is characterized by an XRPD pattern comprising the peaks in Table 4.
[0175] Table 4
[0176]
[0177]
[0178] The XRPD peaks characteristic of each of the free base crystalline Forms I-IV disclosed herein are shown in Table 5.
[0179] Table 5
[0180]
[0181] Hydrochloride salt form: The hydrochloride salt form was initially prepared by precipitation from MTBE and water containing 37 wt% hydrochloric acid. Upon exposure to water or slurrying in water during moisture sorption experiments (hygroscopicity), the salt disproportionated to the free form.
[0182] The hydrochloride salt form is characterized by an XRPD pattern comprising the peaks in Table 6.
[0183] Table 6
[0184]
[0185]
[0186] Dichloromethane Solvate: Dichloromethane solvate Form I was prepared by evaporation from dichloromethane (100 mg / mL) at ambient temperature. The solvate desolvated to free Form I at about 75 °C.
[0187] The dichloromethane solvate is characterized by an XRPD pattern comprising the peaks in Table 7.
[0188] Table 7
[0189]
[0190]
[0191] Nitromethane Solvate: Nitromethane solvate Form I was prepared by evaporation from nitromethane (44 mg / mL) under ambient conditions. The solvate desolvated to free Form I at about 81-97 °C.
[0192] The dichloromethane solvate is characterized by an XRPD pattern comprising the peaks in Table 8.
[0193] Table 8
[0194]
[0195]
[0196] Hexafluoro-2-propanol solvate: Hexafluoro-2-propanol solvate Form I was prepared by a solvent drop crystallization method (sonication of approximately 5 mg and 50 μL hexafluoro-2-propanol for 60 minutes). The solvate desolvated to free Form I at about 83-100 °C.
[0197] Hexafluoro-2-propanol solvate is characterized by an XRPD pattern comprising the peaks in Table 9.
[0198] Table 9
[0199]
[0200] Compound A and propyl gallate co-crystals: Propyl gallate co-crystals were prepared by liquid-assisted grinding of Compound A (30 mg) with 1 molar equivalent of propyl gallate and 5 μL of solvent (EtOH) in a Fritsch planetary mill with 2 small ball bearings at 500 rpm for 2 hours. The sample was then treated with toluene (500 μL) and matured by cycling the temperature from room temperature to 50° C. for six 4-hour cycles, followed by holding at 5° C. for 48 hours. The isolated solid was identified as propyl gallate co-crystals.
[0201] This co-crystal was also prepared by liquid-assisted grinding of Compound A (30 mg) with 1 molar equivalent of propyl gallate and 5 μL of solvent (EtOAc) in a Fritsch planetary mill with 2 small ball bearings at 500 rpm for 2 hours. The isolated solid was identified as propyl gallate co-crystal.
[0202] 1H NMR confirmed the chemical structure and the presence of about 2.0 molar equivalents of propyl gallate and about 0.07 molar equivalents of residual EtOAc.
[0203] Propyl gallate cocrystal NMR:1 H NMR(400MHz, DMSO-d6)δppm0.33-0.41(m,2H)0.42-0.50(m,1H)0.54-0.62(m,1H)0.70-0.82(m,1H)0.91-0.99(m,3H)1.07-1.13(m,1 H)1.15-1.27(m,1H)1.61-1.80(m,4H)1.97-2.00(m,1H)2.53-2.64(m,1H)3.33-3.43(m,4H)3.71-3.77(m,1H)3.99-4.06(m,1H)4.08 -4.15(m,2H)4.48-4.57(m,1H)4.67-4.73(m,1H)4.91-4.99(m,1H)6.92-6.97(m,2H)7.43-7.50(m,1H)7.55-7.63(m,1H)7.69-7.74( m,1H)7.74-7.81(m,1H)8.29-8.33(m,1H)8.47-8.51(m,1H)8.71-8.80(m,1H)8.85-8.90(m,1H)9.11-9.16(m,1H)9.18-9.24(m,1H).
[0204] The propyl gallate co-crystals are characterized by an XRPD pattern comprising the peaks in Table 10.
[0205] Table 10
[0206]
[0207]
[0208] Compound A and glycerol co-crystals: Glycerol co-crystals were prepared by liquid-assisted grinding of Compound A (30 mg) with 1 molar equivalent of propyl gallate and 5 μL of solvent (EtOAc) in a Fritsch planetary mill with 2 small ball bearings at 500 rpm for 2 hours. The sample was then treated with acetone (500 μL) and matured by cycling the temperature from room temperature to 50°C for six 4-hour cycles, followed by holding at 5°C for 48 hours. The isolated solid was identified as the glycerol co-crystal.
[0209] 1H NMR confirmed the chemical structure and the presence of about 2.6 molar equivalents of glycerol and about 0.11 molar equivalents of residual acetone. Storage at 40°C / 75%RH for 7 days was stable according to XRPD.
[0210] Glycerol co-crystal NMR: 1H NMR(400MHz, DMSO-d6)δppm 0.37(br s,2H)0.46(br t,J=8.72Hz,1H)0.57(br s,1H)0.77(br d,J=8.84Hz,1H)1.10(br d,J=2.53Hz,1H)1.73(brs,1H)1.74-1.74(m,1H)1.77(d,J=3.54Hz,1H)2.07(s, 1H)3.23-3.31(m,4H)3.24-3.31(m,1H)3.27-3.31(m,1H)3.31-3.46(m,23H)3.35 -3.46(m,1H)3.49-3.52(m,1H)3.71-3.77(m,1H)4.07(t,J=8.34Hz,1H)4.40(t, J=5.68Hz, 5H) 4.48 (d, J=4.80Hz, 3H) 4.52 (t, J=7.96Hz, 1H) 4.70 (dd, J=11.24, 2. 65Hz,1H)4.95(dd,J=11.49,3.66Hz,1H)7.46(dd,J=10.74,5.68Hz,1H)7.59(dd ,J=10.99,5.43Hz,1H)7.72(dd,J=9.47,5.94Hz,1H)7.77(dd,J=9.35,5.81Hz,1H )8.31(t,J=2.15Hz,1H)8.49(t,J=2.15Hz,1H)8.53(d,J=7.83Hz,1H)8.75(d,J= 7.58Hz, 1H) 8.87 (d, J = 2.02Hz, 1H) 9.13 (d, J = 2.02Hz, 1H) 9.21 (d, J = 2.27Hz, 1H).
[0211] The co-crystals of Compound A and glycerol are characterized by an XRPD pattern comprising the peaks in Table 11.
[0212] Table 11
[0213]
[0214] Compound A and Propylene Glycol Co-crystals: Propylene glycol co-crystals were prepared by liquid-assisted grinding of Compound A (30 mg) with 1 molar equivalent of propylene glycol and 5 μL of solvent (EtOAc) in a Fritsch planetary mill with 2 small ball bearings at 500 rpm for 2 hours. The sample was then treated with acetone (500 μL) and matured by cycling the temperature from room temperature to 50° C. for six 4-hour cycles, followed by holding at 5° C. for 48 hours. The isolated solid was identified as the propylene glycol co-crystal.
[0215] 1H NMR confirmed the chemical structure and the presence of approximately 1.0 molar equivalent of propylene glycol. Storage at 40°C / 75%RH for 7 days was stable according to XRPD.
[0216] Propylene glycol NMR: 1 H NMR (400MHz, DMSO-d6) δppm 0.37 (br s, 2H) 0.42-0.51 (m, 1H) 0.53-0.62 (m, 1H) 0.77 (br d, J = 8.84Hz, 2H) 0.99 (d, J = 6.32Hz, 3H) 1.10 (br d,J=2.53Hz,1H)1.20(br d,J=8.08Hz,1H)1.67-1.79(m,2H)3.10-3.18(m,1H)3.11-3.29(m,1H)3.25(dt,J =10.74,5.49Hz,1H)3.35-3.42(m,4H)3.50-3.61(m,1H)3.70-3.78(m,1H)4.07(br t,J=8.21Hz,1H)4.41(d,J=4.29Hz,1H)4.47(t,J=5.68Hz,1H)4.52(t,J=7.83H z,1H)4.70(brdd,J=11.37,2.53Hz,1H)4.95(dd,J=11.37,3.54Hz,1H)7.46(br dd,J=10.99,5.18Hz,1H)7.59(dd,J=10.99,5.43Hz,1H)7.68-7.73(m,1H)7.77(dd ,J=9.47,5.94Hz,1H)8.28-8.33(m,1H)8.45-8.51(m,1H)8.51-8.56(m,1H)8.75(br d,J=7.33Hz,1H)8.87(d,J=1.77Hz,1H)9.13(d,J=1.77Hz,1H)9.21(d,J=2.02Hz,1H).
[0217] The co-crystals of Compound A and propylene glycol are characterized by an XRPD pattern comprising the peaks in Table 12.
[0218] Table 12
[0219]
[0220]
[0221] Compound A and maltol co-crystals: Maltol co-crystals were prepared by liquid-assisted grinding of Compound A (30 mg) with 1 molar equivalent of maltol and 5 μL of solvent (EtOAc) in a Fritsch planetary mill with 2 small ball bearings at 500 rpm for 2 hours. The sample was then treated with acetone (500 μL) and matured by cycling the temperature from room temperature to 50° C. for six 4-hour cycles, followed by 48 hours at 5° C. The isolated solid was identified as maltol co-crystals.
[0222] 1H NMR confirmed the chemical structure and the presence of about 0.8 molar equivalents of maltol and about 0.14 molar equivalents of residual acetone. Storage at 40°C / 75%RH for 7 days was stable according to XRPD.
[0223] Maltol cocrystal NMR: 1 H NMR(400MHz,DMSO-d6)δppm 0.37(br s,2H)0.42-0.50(m,1H)0.53-0.62(m,1H)0.71-0.81(m,2H)1.07-1.13(m,1H)1.20(br d,J=8.08Hz,1H)1.67-1.79(m,2H)2.07(s,1H)2.24(s,2H)3.36-3.44(m,5H)3.71-3.78(m,1H)4.07(t,J=8.34Hz,1H)4.52(t,J=7.96Hz ,1H)4.70(dd,J=11.37,2.78Hz,1H)4.95(dd,J=11.37,3.54Hz,1H)6.33(d,J=5.56Hz,1H)7.46(dd,J=11.12,5.81Hz,1H)7.59(dd,J=10 .86,5.56Hz,1H)7.72(dd,J=9.47,5.94Hz,1H)7.77(dd,J=9.35,5.81Hz,1H)8.03(d,J=5.56Hz,1H)8.31(t,J=2.15Hz,1H)8.49(t,J=2. 15Hz, 1H) 8.53 (d, J = 7.58Hz, 1H) 8.75 (d, J = 7.33Hz, 1H) 8.84 (s, 1H) 8.87 (d, J = 2.02Hz, 1H) 9.13 (d, J = 1.77Hz, 1H) 9.21 (d, J = 2.27Hz, 1H).
[0224] 1H NMR confirmed the chemical structure and the presence of approximately 1.0 molar equivalent of propylene glycol. Storage at 40°C / 75%RH for 7 days was stable according to XRPD.
[0225] The co-crystals of Compound A and maltol are characterized by an XRPD pattern comprising the peaks in Table 13.
[0226] Table 13
[0227]
[0228] Compound A and urea co-crystals: Urea co-crystals were prepared by liquid-assisted grinding of Compound A (30 mg) with 1 molar equivalent of urea and 5 μL of solvent (EtOH or EtOAc) in a Fritsch planetary mill with 2 small ball bearings at 500 rpm for 2 hours. The isolated solid was identified as urea co-crystal.
[0229] 1H NMR confirmed the chemical structure and the presence of approximately 1.0 molar equivalent of urea. Storage at 25°C / 97%RH and 40°C / 75%RH for 7 days was stable according to XRPD.
[0230] Urea cocrystal NMR: 1 H NMR(400MHz, DMSO-d6)δppm-0.21(br dd,J=8.84,4.55Hz,1H)-0.07-0.03(m,1H)0.37(br s,1H)0.46(br t,J=8.59Hz,1H)0.53-0.61(m,1H)0.77(td,J=8.97,4.80Hz,1H)1.10(td,J=5.05,2.78Hz,1H)1.15-1.26(m,1H)1.5 8-1.64(m,1H)1.67-1.79(m,2H)3.35-3.42(m,4H)3.68-3.79(m,1H)4.02-4.11(m,1H)4.52(t,J=7.96Hz,1H)4.70(br dd,J=11.24,2.65Hz,1H)4.95(dd,J=11.37,3.54Hz,1H)5.40(br s,3H)5.35-5.47(m,1H)6.55(s,1H)7.46(dd,J=11.24,5.68Hz,1H)7.59(dd,J=10.99,5.43Hz,1H)7.69-7.82(m,1H)8.31(t,J=2.15Hz,1H ) 8.49 (t, J = 2.02Hz, 1H) 8.53 (d, J = 7.58Hz, 1H) 8.75 (d, J = 7.33Hz, 1H) 8.87 (d, J = 2.02Hz, 1H) 9.13 (d, J = 2.02Hz, 1H) 9.21 (d, J = 2.27Hz, 1H).
[0231] The co-crystals of Compound A and urea are characterized by an XRPD pattern comprising the peaks in Table 14.
[0232] Table 14
[0233]
[0234]
[0235] Amorphous form: Compound A (300 mg) was dissolved in tBuOH:H2O (1:1, 30 vol) at 50°C. The clear solution was filtered to remove any undissolved particles that could act as nucleation sites. The filtered solution was immediately frozen in a dry ice / acetone bath and placed on a freeze dryer for freeze drying. The resulting solid was analyzed by XRPD.
[0236] 1H NMR confirmed the structure with about 0.39 molar equivalents of residual tBuOH. TGA indicated 2.9% w / w between 50°C-96°C, which corresponds to about 0.22 molar equivalents of residual tBuOH. Crystallized within 1 week after static storage at 80°C / 0%RH or 40°C / 75%RH.
[0237] Amorphous crystalline form NMR: 1 H NMR(400MHz, DMSO-d6)δppm-0.31-0.06(m,1H)-0.28--0.14(m,1H)-0.12-0.04(m,1H)-0.10-0.04(m,1H)-0.09-0.04(m,1H)0.37(br s,3H)0.52-0.67(m,1H)0.68-0.84(m,2H)1.07-1.23(m,6H)1.57-1.79(m,3H)2.30-2.36(m,1H)2.53-2.79(m, 2H)3.68-3.79(m,1H)4.20(s,1H)4.15-4.24(m,1H)4.52(t,J=7.96Hz,1H)4.64-4.78(m,1H)4.95(dd,J=11.37 ,3.54Hz,1H)7.41-7.52(m,1H)7.59(dd,J=11.12,5.56Hz,1H)7.77(dd,J=9.47,5.94Hz,2H)8.27-8.34(m,1H) 8.49 (t, J = 2.15Hz, 2H) 8.76 (d, J = 7.33Hz, 1H) 8.87 (d, J = 1.77Hz, 1H) 9.10-9.17 (m, 1H) 9.21 (d, J = 2.27Hz, 1H).
Claims
1. A free base anhydrous crystalline form of Compound A, i.e. Form I, characterized in that The X-ray powder diffraction pattern contains peaks at 9.78, 12.45, 15.70, 16.46 and 16.94 ± 0.2° 2θ using Cu Kα radiation, Wherein compound A is:
2. The crystalline form of claim 1, further characterized in that Using Cu Ka radiation, there are XRPD pattern peaks at 8.23, 24.40, 25.03, 25.49 and 32.03 ± 0.2° 2θ.
3. The crystalline form of claim 2, further characterized in that Using Cu Ka radiation, there are XRPD pattern peaks at 19.56, 20.11, 22.99, 23.97, 29.53, 41.91, and 42.83 ± 0.2° 2θ.
4. The crystalline form of any one of claims 1 to 3, having an XRPD pattern substantially as shown in Figure 1.
5. The crystalline form of any one of claims 1 to 4, having an endothermic transition at 147 to 157°C as measured by differential scanning calorimetry.
6. The crystalline form of claim 5, wherein the endothermic transition is at 152°C ± 3°C.
7. The crystalline form of any one of claims 1 to 6 having a dynamic vapour sorption substantially as shown in Figure 4.
8. The crystalline form of any one of claims 1 to 7 having a thermogravimetric analysis substantially as shown in Figure 3.
9. A free base anhydrous crystalline form of Compound A, Form II, characterized in that The X-ray powder diffraction pattern contains peaks at 7.67, 11.54, 18.27 and 23.28 ± 0.2° 2θ using Cu Kα radiation, Wherein compound A is:
10. The crystalline form of claim 9, further characterized by Using Cu Ka radiation, there are XRPD pattern peaks at 15.36, 16.33, 18.58, 21.38, 23.59, 24.61, 27.09, 43.40, and 44.26 ± 0.2° 2θ.
11. The crystalline form of claim 10, further characterized by Using Cu Ka radiation, the XRPD pattern had peaks at 18.01, 25.17, 38.15, and 39.26 ± 0.2° 2θ.
12. The crystalline form of any one of claims 9 to 11 having an XRPD pattern substantially as shown in Figure 5.
13. The crystalline form of any one of claims 9 to 12, having an endothermic transition at 175 to 185°C as measured by differential scanning calorimetry.
14. The crystalline form of claim 13, wherein the endothermic transition is at 181°C ± 3°C.
15. A crystalline form of the free base monohydrate of Compound A, Form III, characterized in that The X-ray powder diffraction pattern contains peaks at 7.31, 10.77 and 13.96 ± 0.2° 2θ using Cu Kα radiation, Wherein compound A is:
16. The crystalline form of claim 15, further characterized by Using Cu Ka radiation, there are XRPD pattern peaks at 16.60, 18.56, 18.84, 19.41, 20.57, 21.61, 21.92, 22.28, 23.34, 24.23, 24.70, 25.69, and 28.87 ± 0.2° 2θ.
17. The crystalline form of claim 16, further characterized by Using Cu Ka radiation, the XRPD pattern had peaks at 7.94, 20.10, 23.88, and 28.38 ± 0.2° 2θ.
18. The crystalline form of any one of claims 15 to 17 having an XRPD pattern substantially as shown in Figure 6.
19. The crystalline form of any one of claims 15 to 18, having an endothermic transition at 127°C to 137°C as measured by differential scanning calorimetry.
20. The crystalline form of claim 19, wherein the endothermic transition is at 132°C ± 3°C.
21. The crystalline form of any one of claims 15 to 20 having a dynamic vapour sorption substantially as shown in Figure 9.
22. The crystalline form of any one of claims 15 to 21 having a thermogravimetric analysis substantially as shown in Figure 8.
23. A free base anhydrous crystalline form of Compound A, Form IV, characterized in that The X-ray powder diffraction pattern contains peaks at 8.06, 11.29 and 14.97 ± 0.2° 2θ using Cu Kα radiation, Wherein compound A is:
24. The crystalline form of claim 23, further characterized by Using Cu Ka radiation, there are XRPD pattern peaks at 17.19, 17.63, 18.39, 18.95, 19.17, 20.50, 24.87, 26.03, 26.62, 27.99, and 29.25 ± 0.2° 2θ.
25. The crystalline form of claim 24, further characterized by Using Cu Ka radiation, there are XRPD pattern peaks at 12.08, 20.17, 22.37, 22.86, 25.69, 28.26, and 28.73 ± 0.2° 2θ.
26. The crystalline form of any one of claims 23 to 25, having an XRPD pattern substantially as shown in Figure 10.
27. The crystalline form of any one of claims 23 to 26, having an endothermic transition at 160 to 175°C as measured by differential scanning calorimetry.
28. The crystalline form of claim 27, wherein the endothermic transition is at 167°C ± 3°C.
29. The crystalline form of any one of claims 23 to 28 having a dynamic vapour sorption substantially as shown in Figure 13.
30. The crystalline form of any one of claims 23 to 29 having a thermogravimetric analysis substantially as shown in Figure 12.
31. A crystalline form of compound A hydrochloride, characterized in that The X-ray powder diffraction pattern contains peaks at 8.45, 16.93, 23.74, 24.59 and 26.57 ± 0.2° 2θ using Cu Kα radiation, Wherein compound A is:
32. The crystalline form of claim 31, further characterized by XRPD pattern peaks at 17.33, 17.76, 18.75, 19.51, 19.81, 20.53, 21.36, 22.95, 25.28, 25.89, 26.94, 27.44, and 29.41 ± 0.2° 2θ using Cu Ka radiation.
33. The crystalline form of claim 32, further characterized by Using Cu Ka radiation, the XRPD pattern had peaks at 8.74, 16.08, 19.81 and 28.58 ± 0.2° 2θ.
34. The crystalline form of any one of claims 31 to 33, having an XRPD pattern substantially as shown in Figure 16.
35. The crystalline form of any one of claims 31 to 34, having an endothermic transition at 125°C to 140°C as measured by differential scanning calorimetry.
36. The crystalline form of claim 35, wherein the endothermic transition is at 134°C ± 3°C.
37. The crystalline form of any one of claims 31 to 36 having a dynamic vapor sorption substantially as shown in Figure 19.
38. The crystalline form of any one of claims 31 to 37 having a thermogravimetric analysis substantially as shown in Figure 18.
39. A crystalline form of compound A and dichloromethane, characterized in that The X-ray powder diffraction pattern contains peaks at 11.46, 16.91, 23.10 and 24.58 ± 0.2° 2θ using Cu Kα radiation, Wherein compound A is:
40. The crystalline form of claim 39, further characterized by Using Cu Ka radiation, there are XRPD pattern peaks at 8.25, 16.26, 18.82, 19.50, 19.90, 20.52, 20.79, 21.58, 23.92, and 29.35 ± 0.2° 2θ.
41. The crystalline form of claim 40, further characterized by Using Cu Ka radiation, there are XRPD pattern peaks at 6.76, 25.18, 26.20, 26.95, 27.18, 27.62, and 28.26 ± 0.2° 2θ.
42. The crystalline form of any one of claims 39 to 41 having an XRPD pattern substantially as shown in Figure 20.
43. The crystalline form of any one of claims 39 to 42, having an endothermic transition at 70 to 80°C as measured by differential scanning calorimetry.
44. The crystalline form of claim 43, wherein the endothermic transition is at 76°C ± 3°C.
45. The crystalline form of any one of claims 39 to 44, having a thermogravimetric analysis substantially as shown in Figure 22.
46. A crystalline form of compound A and nitromethane, characterized in that The X-ray powder diffraction pattern contains peaks at 8.94, 15.86, 17.12, 19.51, 19.83 and 24.41 ± 0.2° 2θ using Cu Kα radiation, Wherein compound A is:
47. The crystalline form of claim 46, further characterized by Using Cu Ka radiation, there are XRPD pattern peaks at 10.18, 18.16, 20.54, 21.93, 23.06, 23.92, and 25.37 ± 0.2° 2θ.
48. The crystalline form of claim 47, further characterized by Using Cu Ka radiation, the XRPD pattern had peaks at 19.01, 22.68, 26.61 and 28.32 ± 0.2° 2θ.
49. The crystalline form of any one of claims 46 to 48, having an XRPD pattern substantially as shown in Figure 23.
50. The crystalline form of any one of claims 46 to 49, having an endothermic transition at 81 to 97°C as measured by differential scanning calorimetry.
51. The crystalline form of claim 50, wherein the endothermic transition is at 89°C ± 3°C.
52. The crystalline form of any one of claims 46 to 51 having a thermogravimetric analysis substantially as shown in Figure 25.
53. A crystalline form of compound A and hexafluoro-2-propanol, characterized in that The X-ray powder diffraction pattern contains peaks at 16.17, 16.70, 18.20 and 23.03 ± 0.2° 2θ using Cu Kα radiation, Wherein compound A is:
54. The crystalline form of claim 53, further characterized by Using Cu Ka radiation, the XRPD pattern had peaks at 9.49, 11.20, 20.18, 21.39 23.74, 25.46, 27.00, 29.24 and 33.76 ± 0.2° 2θ.
55. The crystalline form of claim 53 or 54, having an XRPD pattern substantially as shown in Figure 26.
56. The crystalline form of any one of claims 53 to 55, having an endothermic transition at 85 to 95°C as measured by differential scanning calorimetry.
57. The crystalline form of claim 56, wherein the endothermic transition is at 90°C ± 3°C.
58. The crystalline form of any one of claims 53 to 57, having a thermogravimetric analysis substantially as shown in Figure 28.
59. A co-crystal comprising Compound A and a coformer, Wherein compound A is:
60. The co-crystal of claim 59, wherein the coformer comprises benzoic acid, oxalic acid, malonic acid, succinic acid, maleic acid, fumaric acid, glutaric acid, adipic acid, pimelic acid, 3,5-dihydroxybenzoic acid, trifluoroacetic acid, 2,5-dihydroxybenzoic acid, 2,4-dihydroxybenzoic acid, m-nitrobenzoic acid, 5-chlorosalicylic acid, saccharin, citric acid, tartaric acid, 2,3-dihydroxybenzoic acid, 3,4-dihydroxybenzoic acid, barbital, 4-hydroxybenzoic acid, 1-hydroxy-2-naphthoic acid, malic acid, 3-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, methyl gallate, salicylic acid, 2-hydroxybenzoic acid, formic acid, 3-hydroxy-2-naphthoic acid, sulfoacetamide, acetic acid, sulfoacetamide Amineproline, sulfuric acid, aminosulfonic acid, ethylenediamine, octadecylamine, glucono-delta lactone, allocitric acid, sucralose, indole, 1-hydroxyethylidene-1,1-diphosphonic acid, skatole, 5-chlorosalicylic acid, urea, 5-nitroisophthalic acid, trimesic acid, gentisic acid, ketoglutaric acid, adamantanetricarboxylic acid, tert-butylhydroquinone, isocitric acid, trifluoroethanol, camphoric acid, 4-aminobenzoic acid, 2,6-pyridinedicarboxylic acid, aspirin, butyric acid, formamide, nicotinamide, nitromethane, 1,4-benzoquinone, glycolic acid, terephthalaldehyde, dioxane, N-methylpyrrolidone, dimethyl sulfoxide, dimethylacetamide, acetone, dimethylformamide, furfural, 4,4'-bipyridine, or a mixture thereof.
61. The co-crystal of claim 60, wherein the coformer comprises propyl gallate, glycerol, propylene glycol, maltol, urea, or mixtures thereof.
62. The co-crystal of claim 59, wherein the coformer comprises propyl gallate.
63. The co-crystal of claim 62, characterized in that The X-ray powder diffraction pattern comprises peaks at 8.66, 15.00, 17.72, 18.82 and 20.32 ± 0.2° 2θ using Cu Kα radiation.
64. The co-crystal of claim 63, further characterized by Using Cu Ka radiation, the XRPD pattern had peaks at 9.21, 19.36, 20.49 and 22.57 ± 0.2° 2θ.
65. The co-crystal of claim 64, further characterized by Using Cu Ka radiation, there are XRPD pattern peaks at 3.05, 11.24, 18.32, 21.73, 22.98, 23.39, 25.01, 25.51, 26.30, 26.52, and 28.31 ± 0.2° 2θ.
66. The co-crystal of any one of claims 63 to 65 having an XRPD pattern substantially as shown in Figure 29.
67. The co-crystal of any one of claims 62 to 66 having an endothermic transition at 116 to 126°C as measured by differential scanning calorimetry.
68. The co-crystal of claim 67, wherein the endothermic transition is at 121 °C ± 3 °C.
69. The co-crystal of any one of claims 62 to 68 having a thermogravimetric analysis substantially as shown in Figure 31.
70. The co-crystal of claim 59, wherein the coformer comprises glycerol.
71. The co-crystal of claim 70, characterized in that The X-ray powder diffraction pattern comprises peaks at 16.84, 18.48, 19.40 and 21.49 ± 0.2° 2θ using Cu Kα radiation.
72. The co-crystal of claim 71, further characterized by Using Cu Ka radiation, there are XRPD pattern peaks at 9.70, 15.60, 16.39, 18.95, 22.51, 24.53 and 24.92 ± 0.2° 2θ.
73. The co-crystal of claim 72, further characterized by Using Cu Ka radiation, the XRPD pattern had peaks at 8.17, 12.38, 22.87, and 27.61 ± 0.2° 2θ.
74. The co-crystal of any one of claims 71 to 73 having an XRPD pattern substantially as shown in Figure 32.
75. The co-crystal of any one of claims 70 to 74 having endothermic transitions at 140-151 °C and 152-165 °C as measured by differential scanning calorimetry.
76. The co-crystal of claim 75, wherein the endothermic transitions are at 148°C ± 3°C and 156°C ± 3°C.
77. The co-crystal of any one of claims 70 to 76 having a thermogravimetric analysis substantially as shown in Figure 34.
78. The co-crystal of claim 59, wherein the coformer comprises propylene glycol.
79. The co-crystal of claim 78, characterized in that The X-ray powder diffraction pattern comprises peaks at 16.82, 18.26, 18.93, 19.37 and 21.52 ± 0.2° 2θ using Cu Kα radiation.
80. The co-crystal of claim 79, further characterized by Using Cu Ka radiation, there are XRPD pattern peaks at 7.87, 15.61, 16.36, 18.39, 20.39, 21.12, 22.47, and 24.46 ± 0.2° 2θ.
81. The co-crystal of claim 80, further characterized by Using Cu Ka radiation, there are XRPD pattern peaks at 9.69, 20.02, 21.83, 22.85, 23.84, 25.05, and 27.07 ± 0.2° 2θ.
82. The co-crystal of any one of claims 79 to 81 having an XRPD pattern substantially as shown in Figure 35.
83. The co-crystal of any one of claims 78 to 82 having a broad dissociation endothermic transition at 80 to 135°C as measured by differential scanning calorimetry.
84. The co-crystal of claim 83, wherein the broad endothermic transition is at 89 to 124°C ± 3°C.
85. The co-crystal of any one of claims 78 to 84 having a thermogravimetric analysis substantially as shown in Figure 37.
86. The co-crystal of claim 59, wherein the coformer comprises maltol.
87. The co-crystal of claim 86, characterized in that The X-ray powder diffraction pattern comprises peaks at 16.85, 18.18, 19.53 and 23.54 ± 0.2° 2θ using Cu Kα radiation.
88. The co-crystal of claim 87, further characterized by Using Cu Ka radiation, there are XRPD pattern peaks at 6.58, 8.86, 13.68, 14.60, 15.25, 21.52, 25.26, and 26.63 ± 0.2° 2θ.
89. The co-crystal of claim 88, further characterized by Using Cu Ka radiation, the XRPD pattern had peaks at 4.44, 7.98 and 13.13 ± 0.2° 2θ.
90. The co-crystal of any one of claims 87 to 89 having an XRPD pattern substantially as shown in Figure 38.
91. The co-crystal of any one of claims 86 to 90 having a broad dissociation endothermic transition at 125-135°C as measured by differential scanning calorimetry.
92. The co-crystal of claim 91, wherein the broad endothermic transition is at 130°C ± 3°C.
93. The co-crystal of any one of claims 86 to 92 having a thermogravimetric analysis substantially as shown in Figure 40.
94. The co-crystal of claim 59, wherein the coformer comprises urea.
95. The co-crystal of claim 94, characterized in that The X-ray powder diffraction pattern comprises peaks at 3.99, 11.24, 17.62 and 18.37 ± 0.2° 2θ using Cu Kα radiation.
96. The co-crystal of claim 95, further characterized by Using Cu Ka radiation, there were XRPD pattern peaks at 8.01, 8.39, 14.96, 17.47, 18.94, 19.13, 20.51, 24.65, 24.86, 25.70, 25.97, and 26.62 ± 0.2° 2θ.
97. The co-crystal of claim 96, further characterized by Using Cu Ka radiation, there are XRPD pattern peaks at 15.21, 16.93, 17.16, 22.37, 26.35, 28.01, 28.26, 28.77, and 29.25 ± 0.2° 2θ.
98. The co-crystal of any one of claims 95 to 97 having an XRPD pattern substantially as shown in Figure 41.
99. The co-crystal of any one of claims 94 to 98 having dissociation endothermic transitions at 160-170°C and 171-180°C as measured by differential scanning calorimetry.
100. The co-crystal of claim 99, wherein the endothermic transitions are at 167°C ± 3°C and 174°C ± 3°C.
101. The co-crystal of any one of claims 94 to 100 having a thermogravimetric analysis substantially as shown in Figure 43.
102. A pharmaceutical composition comprising the crystalline form or co-crystal of Compound A according to any one of claims 1 to 101 and a pharmaceutically acceptable carrier.
103. Use of the crystalline form or co-crystal of Compound A as claimed in any one of claims 1 to 101 or the composition of claim 102 in the preparation of a medicament for treating heart failure in a subject in need thereof.
